Bloomfield, Mo., Rev. Ordinances ch. 12, art. 3, § 52 (1898) - (:unkn) unknown (My University, 1898)
Ch. 12, Art. 3, § 52: It shall be unlawful for any person in this city, except he be a police officer of this city or other officer in the discharge of his official duty, to discharge or fire off any gun, pistol or fire-arms of any description within the corporate limits of this city, and every person violating this section, shall, upon conviction, be deemed guilty of a misde§meanor and punished by a fine of not less than five nor more than twenty dollars, or by imprisonment in the city calaboose not exceed§ing twenty days."
Keywords: DISCHARGE